Newsroom Convergence and Local Media Economic Sustainability Strategy: A Comparative Study of Tribun Pekanbaru and Riau Pos in the Digital Transformation Era - Rinal Sagita; Belli Nasution; Muhammad Firdaus (PT. Maju Malaqbi Makkarana, 2026)
This study aims to analyze newsroom convergence processes and newsroom models implemented by Tribun Pekanbaru and Riau Pos, while also examining how newsroom convergence is utilized as an economic strategy to maintain the sustainability of local media businesses amid digital disruption. The research employed a qualitative descriptive approach through in-depth interviews, observation, and documentation studies involving newsroom managers, editors, and journalists from both media organizations. The findings indicate that Tribun Pekanbaru and Riau Pos have adopted different newsroom convergence strategies. Tribun Pekanbaru has implemented an integrated newsroom model that combines Cross Media Newsroom and Integrated Media Newsroom approaches, emphasizing digital-first production and multi-platform content distribution. Meanwhile, Riau Pos continues to maintain a separated newsroom model between print and digital divisions, reflecting a gradual adaptation process toward digital transformation. The study further reveals that these differences are influenced not only by technological factors and organizational culture but also by economic considerations. Tribun Pekanbaru develops an integrated newsroom to improve production efficiency and expand digital content monetization, while Riau Pos maintains separated newsrooms because print media remains a significant source of company revenue. This study concludes that newsroom convergence has evolved beyond a technological transformation into an economic adaptation strategy for local media organizations. The findings suggest that newsroom convergence enables media companies to improve operational efficiency, broaden audience reach, optimize resource utilization, and strengthen business sustainability in an increasingly competitive digital environment.